Enhancing Energy Efficiency of Maleic Anhydride Production via Heat Integration and Feed Preheating - Vania Durrotun Nafisah; Stefani Lieliani; Khansa Huwaida; Mira Khairunnisa; Balqis Chaula Najma (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
This study explores strategies to enhance energy efficiency in maleic anhydride production through heat integration and feed preheating modifications within an existing process configuration. The process, based on benzene oxidation in a plug flow reactor followed by absorption and distillation, was modeled under steady state conditions to evaluate energy utilization across key unit operations. In the baseline setup, the reactor feed depended entirely on external heating, while significant thermal energy in the reactor effluent was lost through cooling utilities. To address this inefficiency, a modified configuration was introduced in which part of the effluent heat was redirected to the feed preheater, enabling internal energy recovery and reducing reliance on external utilities. Simulation results demonstrated a marked improvement in energy efficiency, with energy savings rising from 1.219×108 kJ/h (93.93%) to 1.625×108 kJ/h (96.04%) after modification. The redistribution of thermal load across the heat exchanger network confirmed that internal heat was effectively harnessed without incurring additional utility costs or capital investment. Overall, these findings highlight heat integration as a practical and economically advantageous approach to improving energy efficiency in maleic anhydride production while preserving operability and separation performance. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).